STRUCTURE OF DEFECTIVE VECTORS FOR ASSOCIATED ENTIRE CURVES WITH LINEARLY DEPENDENT COMPONENTS
We study the structure of the set of exceptional vectors in the sense of Nevanlinna for associated entire curves of finite order with linearly dependent components. It is shown that even if an entire curve has linearly independent components, its associated entire curve may nevertheless have linearly dependent components. It is known that the set of all Nevanlinna exceptional vectors of a finite-order entire curve with linearly dependent components, together with a given subspace